Unified regional European market and its implications challenges the Caribbean. - Stone, Carl (1990)
Points out that the real challenge of Europe to the Caribbean is not in the area of retaining traditional markets, but in funding opportunities for exporting new products and more non-traditional products to what will become by far the world's largest trading centre or marketplace. Calls for joint regional policies between Caribbean government, regional thinking and collaboration by entrepreneurs, and innovative and creative action by Caribbean business interests.